Pengawasan Hukum terhadap Konsumen Atas Produk dalam Hukum Bisnis - Resmina Sinaga; Theresia Oppusunggu; Nibenia Telaumbanua; David Situmorang; Toman Sony Tambunan (Master Manajemen, 2025)
The purpose of this study is to determine the regulations governing consumer supervision of beauty products in business law and to determine the implementation of legal entity supervision of consumers of a product in Indonesia. This study uses a qualitative research approach method using data analysis techniques, namely the theory of Miles, Hubersman and Sandana. The results of this study are the regulations and laws that form the basis for legal supervision of consumers of beauty products written in the business law where the implementation of legal entity supervision of consumers in the use of beauty products in Indonesia still faces various challenges, both in terms of regulation, law enforcement, and public awareness, especially in dealing with the rampant circulation of illegal products and misleading advertisements, especially on digital platforms. Weak supervision in the field and low public literacy are also factors that worsen the situation. Therefore, this study suggests the need for improvements by the government in enforcing legal regulations and awareness from business actors and consumers to create more effective supervision.